The Economic Effects of Density: A Synthesis - Gabriel Ahlfeldt; Elisabetta Pietrostefani (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper synthesises the state of knowledge on the economic effects of density. We consider 15 outcome categories and 209 estimates of density elasticities from 103 studies. More than 50% of these estimates have not been previously published and have been provided by authors on request or inferred from published results in auxiliary analyses. We contribute own estimates of density elasticities of 16 distinct outcome variables that belong to categories where the evidence base is thin, inconsistent or non-existent. Along with a critical discussion of the quality and the quantity of the evidence base we present a set of recommended elasticities. Applying them to a scenario that roughly corresponds to an average high-income city, we find that a 1% increase in density implies positive per capita net present values of wage and rent effects of 280 and 485. The decrease in real wage net of taxes of 342 is partially compensated for by an aggregate amenity effect of 221 and there is a positive external welfare effect of 52. Density has important positive amenity and resource implications, but also appears to create a scarcity rent, which harms renters and first-time buyers.
Keywords: R38; R52; R58; 330; compact; city; density; meta-analysis; elasticity; net present value